Melissos of Samos – Doxography and Fragments - Wesoły, Marian A. (Peitho. Examina Antiqua, 2020)
There are several recent and noteworthy studies on the testimonies and fragments of Melissos of Samos: Laks-Most (2016), Brémond (2017). Furthermore, one can learn a great deal about Melissos from the lectures and discussions undertaken in the framework of “Eleatica 2012” (Mansfeld A. et al. 2016). When taken together, these studies enable us to fully appreciate Melissos’ original work in terms of its sources, its audacious arguments and its later criticisms. Melissos is here presented as a spokesman of the Eleatic school in an order that aims to do justice to the ancient testimonies that relate and refute his arguments as well as to the verbatim fragments (these are given here in the original). For the sake of clarity, however, various secondary testimonies have been omitted.